Aplikasi Mobile Augmented Reality Sebagai Media Pembelajaran Senjata Tradisional Jawa dengan Metode Pengembangan RAD - Visco Adam Bramasta; Agus Suhendar (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Traditional weapons are one of the cultural heritages in Indonesia. Culture itself is a way of life and human identity. We must continue to protect and preserve culture so that it does not become extinct over time. Traditional weapons are a cultural heritage that needs to be preserved, one way to preserve them is by teaching school students the history of the traditional weapon culture of each region. Currently, the method of learning and introducing students to the history of traditional weapons is quite monotonous and boring, such as students can study manually through books to find out the history and origins of traditional weapons, or have to go to museums to see the forms of traditional weapons. However, along with the development of modern times, technology can now be used in various ways, one of which is as a learning medium. Therefore, the author created an application for introducing traditional weapons based on mobile augmented reality to increase students' interest in learning about traditional weapons culture on the island of Java. The author took advantage of the opportunity to create an information application about traditional weapons culture on the island of Java with a 3-dimensional augmented reality feature which is useful as a medium for introduction, knowledge and learning about traditional weapons on the island of Java. In making this application the author also used several tools such as unity, vuforia database and blender as a medium for creating 3-dimensional objects